A STUDY REVIEW OF CANNABIS USE WITH CANCER PATIENTS - Kacper Stępniak,; Paulina Krzeszowska,; Adrianna Samoraj,; Jakub Zajączkowski,; Karolina Marrodán-Wojtczak,; Jan Wilk,; Jakub Jarmołowicz,; Aleksandra Kujawa,; Karolina Krochmal,; Radosław Kuźma, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Cancer patients frequently experience debilitating symptoms such as pain, chemotherapy-induced nausea and vomiting (CINV), and cachexia, significantly impacting their quality of life. Cannabinoids have been suggested as potential therapeutic agents for these conditions. Our review takes a look into medical studies to show potential benefits and side effects of the drug.Aim of Study: This systematic review is looking for evidence on the efficacy and safety of cannabinoids in managing chronic cancer pain, CINV, and cancer-related appetite and cachexia.Materials and Methods: A systematic review of PubMed and Google scholar literature was searched using the terms "cannabis" "cancer," and either "pain" or "CCINV” and "cachexia" with studies read for relevance and objectivity.Results: The evidence regarding cannabinoids for chronic cancer pain is mixed, with some studies suggesting benefits for neuropathic pain, while others show limited efficacy, particularly in opioid-resistant cases. For CINV, certain cannabinoid combinations (e.g., THC:CBD, nabilone) demonstrated effectiveness when standard antiemetics were insufficient, however with potential side effects. The impact of cannabinoids on appetite and cachexia is also inconclusive, with some studies showing potential benefits, but larger trials often failing to demonstrate significant advantages over placebo.Conclusion: There are many myths and disinformation about cannabis in the public eye. Some glorify it, others condemn it. Studies on CINV and neuropathic pain clearly show that cannabis has antiemetic and analgesic properties. Unfortunately, cannabis does not have an analgesic effect in cancer pain, especially when it comes to pain that is resistant to opioid treatment. When it comes to stimulating appetite and cachexia, the research is very inconclusive, and further studies are needed to evaluate this problem.